2014
DOI: 10.6061/clinics/2014(10)05
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the serum and tissue levels of oxidative stress markers and the extent of inflammation in acute appendicitis

Abstract: OBJECTIVES:To determine the serum and tissue levels of markers of impaired oxidative metabolism and correlate these levels with the histopathology and Alvarado score of acute appendicitis patients.METHOD:Sixty-five acute appendicitis patients (mean age, 31.4±12.06 years; male/female, 30/35) and 30 healthy control subjects were studied. The Alvarado score was recorded. Serum samples were obtained before surgery and 12 hours postoperatively to examine the total antioxidant status, total oxidant status, paraoxona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 18 publications
4
41
0
Order By: Relevance
“…[9,17] Many studies have been performed affirming general validity for predicting acute appendicitis. Dumlu et al [18] stated in a study they performed that as Alvarado score increased, inflammation also increased. In a study performed by Kariman et al, [19] patients who presented with acute abdominal pain and had result greater than 7 on Alvarado scoring system were 93% more likely to be diagnosed with acute appendicitis, while patients with score below 7 had 26% chance of being diagnosed with acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,17] Many studies have been performed affirming general validity for predicting acute appendicitis. Dumlu et al [18] stated in a study they performed that as Alvarado score increased, inflammation also increased. In a study performed by Kariman et al, [19] patients who presented with acute abdominal pain and had result greater than 7 on Alvarado scoring system were 93% more likely to be diagnosed with acute appendicitis, while patients with score below 7 had 26% chance of being diagnosed with acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…No strong correlation was observed in their findings despite statistical significance. Dumlu et al [18] classified patient groups in terms of severity of inflammation as having acute appendicitis, perforated appendix, perforation + phlegmonous appendicitis, or perforated appendix and negative appendectomy. Correlation was observed between severity of inflammation and Alvarado scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors found no correlation between the pathological extent of acute appendicitis and oxidative stress markers. [26] In another study, plasma IMA level was found to be significantly higher in acute mesenteric ischemia in comparison to the nonoccluded group, suggesting that IMA might have a diagnostic value in acute thromboembolic occlusion of mesenteric vessels. [2] In the literature, there are only two studies on the association between IMA and AP.…”
Section: Discussionmentioning
confidence: 99%
“…[2,26,27] In one of those, serum levels of oxidative stress markers including IMA were found to be higher in patients with acute appendicitis than in healthy individuals. However, the authors found no correlation between the pathological extent of acute appendicitis and oxidative stress markers.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the balance between oxidants and antioxidants is crucial in the pathogenesis of AA (5). However, whether oxidative stress is caused by an inflammatory response or an increase in free radicals is sufficient for activating the enzymatic defense system is not clear (6).…”
Section: Introductionmentioning
confidence: 99%